ICTs in Learning in Pakistan - Taimur Ul Hassan; Abdul Rahim Sajid (International Journal of Evaluation and Research in Education (IJERE), 2012)
The paper investigates the barriers to the integration of Information and Communication Technologies (ICTs) at the secondary level learning in Pakistan, with focus on Punjab province. Exploring major barriers to the integration of ICTs at the school level, teacher level and student level and possible enablers to these barriers is the major focus of study. Sequential mixed method design is used. Interviews were analysed qualitatively whereas survey questionnaire were analysed quantitatively. It is observed from the findings that most of the participants are having positive perceptions about the integration of ICT into their teaching and learning. Administrators and ICT coordinators revealed many barriers and possible enablers to the integration of ICTs. Many of these barriers are verified by the teachers and students later on however there were some barriers which were not endorsed by the teachers and students.DOI: http://dx.doi.org/10.11591/ijere.v1i2.1244